Introduction to microelectronics to nanoelectronics design and technology - Majumder, Manoj Kumar; Kumbhare, Vijay Rao; Japa, Aditya; Kaushik, Brajesh Kumar (CRC Press, 2021)
Focussing on micro- and nanoelectronics design and technology, this book provides thorough analysis and demonstration, starting from semiconductor devices to VLSI fabrication, designing (analog and digital), on-chip interconnect modeling culminating with emerging non-silicon/ nano devices. It gives detailed description of both theoretical as well as industry standard HSPICE, Verilog, Cadence simulation based real-time modeling approach with focus on fabrication of bulk and nano-devices. Each chapter of this proposed title starts with abrief introduction of the presented topic and ends with a summary indicating the futuristic aspect including practice questions. Aimed at researchers and senior undergraduate/graduate students in electrical and electronics engineering, microelectronics, nanoelectronics and nanotechnology, this book: Provides broad and comprehensive coverage from Microelectronics to Nanoelectronics including design in analog and digital electronics. Includes HDL, and VLSI design going into the nanoelectronics arena. Discusses devices, circuit analysis, design methodology, and real-time simulation based on industry standard HSPICE tool. Explores emerging devices such as FinFETs, Tunnel FETs (TFETs) and CNTFETs including their circuit co-designing. Covers real time illustration using industry standard Verilog, Cadence and Synopsys simulations.